1002 Predicting employee's health and wellbeing: findings from a mass employees health screening program in malaysia. (24th April 2018) - Darus, Azlan; Aziz Mohammed, Mohammed Azman
Abstract : Introduction: The Social Security Organisation of Malaysia is a statutory body responsible for social security protection to employees in Malaysia against occupational injury and diseases, and total inability to earn any income. In the year 2013, SOCSO had embarked on a health promotion campaign to its insured persons by providing free health screening to all insured persons aged 40 years old and above. Until the time of writing, 2.4 million insured persons were eligible and offered the health screening program. Methodology: Presence of cardiovascular risk factors and diseases such as diabetes, hypertension, hypercholesterolaemia and body mass index were obtained from the health screening data Cardiovascular risk factors were determined through Framingham risk scoring computed from the available health parameters. Results: A total of 4 72 093 employee health screening data were available for analysis. There were 53% male compared to 47% female. Among the males, 30% had indicated that they are current smokers, compared to 1% among women. The prevalence of overweight, obesity, hypertension, diabetes and hypercholesterolaemia were 39%, 34%, 27%, 9% and 62% respectively. More than 9800 women were found with highly suspicious mammogram, with 164 found with findings highly suggestive of breast malignancy. Meanwhile, nearly 500 women were found with abnormal pap smear findings, with some found with cervical cancer. Discussion: Malaysia as a nation is facing a new challenge in sustaining the productivity of employees. The findings of the health status of Malaysian employees, showed much higher prevalence of non-communicable disease risk factors compared to what it was 10 years ago. To curb the epidemic and its impact to both businesses and the nation, a concentrated effort involving the government, the employees and the employers are required.